Carbon Lock-In Mechanisms in Transport Infrastructure and Temporal Spatial Dynamics - Yinghui Zhang; Yun Chen; Kai Li; Yong Wu; Chongsen Ma (Buildings)
The persistent carbon lock-in in transport infrastructure hinders low-carbon transition and sustainable urban development. This study, situated within the context of building energy and systems environments, examines the spatial and temporal dynamics of carbon lock-in across Chinese provinces over the past decade. A composite indicator system is constructed to quantify path dependence in transport-related carbon emissions. Additionally, a quantile regression model is applied to analyze the heterogeneous effects of influencing factors across varying levels of lock-in. The findings offer insights into developing region-specific decarbonization strategies and enhancing the sustainability of infrastructure systems. The key findings are as follows: (1) temporally, the composite path dependence index (PDI) increased from 0.13 to 0.24, with an average annual growth rate of 5.7%, although the growth trend exhibited noticeable fluctuations. (2) Spatially, a clear “East-High–West-Low, South-High–North-Low” pattern is observed, with the eastern region exhibiting a PDI approximately 29% higher than that of the northeastern region—mainly due to differences in economic vitality and the degree of policy intervention. (3) Threshold nonlinearity is evident: the influence of key factors on carbon path dependence varies across quantiles, and a critical threshold appears at the 0.9 quantile. Notably, the mitigating effect of low-carbon technological innovation on path dependence weakens beyond this threshold, suggesting diminishing marginal returns and the necessity for complementary governance strategies. This study deepens the understanding of transport carbon lock-in and provides guidance for region-specific strategies to enhance energy efficiency and sustainability in integrated building infrastructure systems.